SENGKETA PENENTUAN BATAS USIA PENSIUN DI PENGADILAN HUBUNGAN INDUSTRIAL - Zulfikar Fahlevi (Jurnal Ilmu dan Budaya, 2019)
In Act No. 13, 2003 on employment stated does not regulate the time of retirement and the retirement age limit for private-sector workers. In article 167 paragraph 1 of the employment LAW is mentioned that one reason for termination of employment is because workers have entered the retirement age.. The results of the research are comprehended, that the retirement age limit is not regulated and expressly stipulated in the Manpower Act, but implied in article 154 letter C of Act No. 13/2003, that the retirement age limit shall be governed or Agreement, company regulation or cooperation agreement, or for certain departments governed by statutory regulations. If not regulated, it can refer to the law that is practiced in some companies, while in the form of legal certainty as an effort to prevent disputes of interest age limit is reviewed from the case 190/PDT.Sus-PHI.G/2018/PN.JKT.PS. The judge's verdict in the case is already reflecting justice because it considers that PKB is an autonomous law made by the entrepreneur with a labor union whose ordinance of manufacture and validity is governed by public law (heteronom) and can be proven by the agreement without leaving a dispute regarding the retirement age.